Co-designing fodder diversification and co-products recycling fosters effectiveness, productivity and agroecological transition of dairy farms in Burkina Faso - Ouattara, Songdah Désiré; Sib, Ollo; Orounladji, Boko Michel; Sanogo, Souleymane; Bougouma-Yameogo, Valérie Marie Christiane; Vall, Eric (Frontiers in Agronomy, 2025)
IntroductionBurkina Faso's dairy farms, whether extensive or semi-intensive, face major sustainability challenges. Introducing agroecological technologies offers an opportunity to optimize the use of local resources and enhance farm resilience and productivity. This study presents an innovative approach that tests and assesses, in co-design with farmers, the integration of two major agroecological technologies that underpin crop–livestock integration.MethodsTo assess the impact of these agroecological technologies, dairy farmers of the Bobo-Dioulasso milkshed implemented on-farm trials involving: (i) the introduction of dual-purpose fodder cereals (maize and sorghum) and legumes (Cowpea and mucuna) for feeding lactating cows, and (ii) the recycling of livestock and crop co-products to produce manure in covered manure pits. We employed a four-step methodological approach for co-designing agroecological innovations with 43 dairy farmers: diagnosis, co-design and experimentation, assessment, and identification of induced changes. Data from experiments and participatory assessment workshops were analyzed to compare dairy farm performance before and after the introduction of agroecological technologies. The first changes induced by these technologies were identified and characterized through participatory workshops.Results and discussionThe introduction of dual-purpose fodder crops into production systems led to improvements in on-farm milk production. Legume fodder storage increased from 356 to 518 kg DM/farm (+45%), while cereal fodder storage decreased slightly (1,388 to 1,091 kg DM/farm). The establishment of covered manure pits enhanced manure quality, with an average increase of 4,679 kg DM/farm. Milk production rose markedly, by over 80% for mixed cows (6.43 vs. 11.67 L/d/cow) and 12% for zebu cows (1.11 vs. 1.25 L/d/cow). Agroecological performance scores also improved particularly in diversity (38% vs. 94% after introduction of agroecological technologies), recycling (31% vs. 88%), and synergy (25% vs. 69%). These results demonstrate that a step-by-step integration of agroecological technologies can enhance their effectiveness and milk productivity, while strengthening the resilience of dairy farms, particularly in the face of climatic and economic challenges. Under conditions of prolonged dry seasons, irregular rainfall, and volatile prices of industrial inputs, the combination of these technologies ensures both the availability of fodder for livestock and manure for soil fertilization. Nevertheless, continued efforts are required to maintain and further improve this performance over time.